Adhesion to Zirconia: A Systematic Review of Current Conditioning Methods and Bonding Materials - Daniele Scaminaci Russo; Francesca Cinelli; Chiara Sarti; Luca Giachetti (MDPI AG, 2019)
Background. Reliable bonding between resin composite cements and high strength ceramics is difficult to achieve because of their chemical inertness and lack of silica content that makes etching impossible. The purpose of this review is to classify and analyze the existing methods and materials suggested to improve the adhesion of zirconia to dental substrate by using composite resins, in order to explore current trends in surface conditioning methods with predictable results. Methods. The current literature, examining the bond strength of zirconia ceramics, and including in vitro studies, clinical studies, and a systematic review, was analyzed. The research in the literature was carried out using PubMed and Cochrane Library databases, only papers in English, published online from 2013 to 2018. The following keywords and their combinations were used: Zirconia, 3Y-TZP, Adhesion, Adhesive cementation, Bonding, Resin, Composite resin, Composite material, Dentin, Enamel. Results. Research, in PubMed and Cochrane Library databases, provided 390 titles with abstracts. From these, a total of 93 publications were chosen for analysis. After a full text evaluation, seven articles were discarded. Therefore, the final sample was 86, including in vitro, clinical studies, and one systematic review. Various adhesive techniques with different testing methods were examined. Conclusions. Airborne-particle abrasion and tribo-chemical silica coating are the pre-treatment methods with more evidence in the literature. Increased adhesion could be expected after physico-chemical conditioning of zirconia. Surface contamination has a negative effect on adhesion. There is no evidence to support a universal adhesion protocol.